Negotiating a Software Career: Informality and “The Lads’ in an Irish Software Installation - Tierney, Margaret (Research Centre for Social Science / University of Edinburgh, 1992)
Despite the glamorous imagery attached to software work, this paper looks at how software workers are not universally equipped to turn their expertise to best effect in pursuing a career in software. It addresses how and why stratified access to key software jobs is critically shaped, and reproduced, by the local social networks of the office. By analysing a detailed case study of an Irish software installation in terms of its recruitment and promotion practices; its informal work environment; and the structures and devices by which staff become identified as 'good material', the paper explores how 'the lads' in the office are best placed to successfully negotiate a rewarding software career.
Keywords: software work; softare workers; expertise; local social networks; office; Ireland; Irish software installation